Exploring the Impact of Virtual Reality and Learning Styles on Student Outcomes: Insights into Synergistic Effects and Academic Success - Degeng, Made Duananda Kartika; Triretnoningrum, Alfin Niken (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study explored the interactive effect between virtual reality-based learning media and student learning styles on student learning outcomes. Although the use of virtual reality (VR) in education is increasingly widespread, research has yet to thoroughly examine how VR-based learning media interact with students’ individual learning styles to influence learning outcomes. VR has demonstrated potential in boosting student engagement and comprehension, especially in subjects rich in content such as learning for type of field of Fact. However, there remains limited understanding of how learners with visual, auditory, and kinesthetic preferences respond uniquely to immersive learning experiences. A quasi-experimental factorial design (2×2) was employed in the study. Participants were divided into two groups that carried out the learning process using VR and video. The results of the study showed that the group learned using VR significantly improved their learning outcomes compared to video. Mixed learning styles students in experiment groups achieved higher average learning outcomes than students with visual or auditory learning styles. Meanwhile, a group of students with auditory learning styles performed better than both visual and mixed learning styles in control group. Furthermore, this research found an interactive effect that significantly affected the connection between instructional media and learning styles in relation to student learning outcomes. As the main purpose of holding why this research was conduct, it is recommended for teachers not to use VR just like that, but must first ensure that students' learning styles are indeed suitable for learning using this media.